Parallel modeling of hygrothermal performance of external wall made of highly perforated bricks. (November 2017) - Maděra, Jiří; Kočí, Jan; Kočí, Václav; Kruis, Jaroslav
Highlights: Parallelization of complicated computational problems is introduced. Schur complement method is utilized, enabling to decompose the problem and solve it on multiple processors at the same time. Practical application is demonstrated on 2D modelling of hygrothermal performance of highly perforated brick with complex geometry. The obtained results indicate that effective parallelization can significantly reduce the computational time. Abstract: Coupled heat and moisture transport in highly perforated bricks is indispensable part of design of energy efficient buildings. Geometry of the perforated bricks is very complicated which results in large number of nodes and elements in numerical analysis. Moreover, material model of the coupled heat and moisture transport leads after discretization to nonsymmetric systems of algebraic equations which need large computer memory. In order to reduce the computational time or to solve problems with many degrees of freedom, parallel computers are employed. Parallelization is based on the Schur complement method which is able to deal with nonsymmetric systems. Example of the coupled heat and moisture transport in a perforated brick of HELUZ company is showed. Real climatic boundary conditions for two different locations are used.